2002
DOI: 10.1074/jbc.m107598200
|View full text |Cite
|
Sign up to set email alerts
|

U2AF Participates in the Binding of TAP (NXF1) to mRNA

Abstract: TAP/NXF1 is a conserved mRNA export receptor serving as a link between messenger ribonucleoproteins (mRNPs) and the nuclear pore complex. The mechanism by which TAP recognizes its export substrate is unclear. We show here that TAP is added to spliced mRNP in human cells. We identified a distinct region of TAP that targets it to mRNP. Using yeast two-hybrid screens and in vitro binding studies, we found that this region coincides with a direct binding site for U2AF35, the small subunit of the splicing factor U2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 58 publications
(83 reference statements)
6
61
0
Order By: Relevance
“…4A, lane 14). Amino acids 61-118 showed a strong RNA cross-linking activity consistent with earlier work (25) and amino acids 1-60 a weaker activity. Within amino acids 61-118 there are a large number of arginines potentially involved in RNA binding, and despite low overall conservation of this region across organisms, TAP orthologs possess a basic region at the N terminus (Fig.…”
Section: The Rna-binding Domain Of Tap Is Required For Its Export Actsupporting
confidence: 79%
See 1 more Smart Citation
“…4A, lane 14). Amino acids 61-118 showed a strong RNA cross-linking activity consistent with earlier work (25) and amino acids 1-60 a weaker activity. Within amino acids 61-118 there are a large number of arginines potentially involved in RNA binding, and despite low overall conservation of this region across organisms, TAP orthologs possess a basic region at the N terminus (Fig.…”
Section: The Rna-binding Domain Of Tap Is Required For Its Export Actsupporting
confidence: 79%
“…Earlier work demonstrated the TAP RNP-type RNA-binding domain (RBD) was dispensable for activity in vivo (23), although it had not been shown that the isolated RBD (amino acids 118-198) bound RNA. Amino Acids 96-198, encompassing the RBD, bind RNA (24), yet a separate study showed that amino acids 61-121 were involved in RNA binding (25). We clarified which region of TAP is responsible for nonspecific RNA binding by using truncations, internal deletions, and mutations (Fig.…”
Section: The Rna-binding Domain Of Tap Is Required For Its Export Actmentioning
confidence: 99%
“…Shuttling RNA-binding proteins may contribute to the assembly of an export competent mRNP by recruiting mRNA export factors. Consistent with this view U2AF 35-kDa subunit (Zolotukhin et al, 2002), several shuttling SR proteins (Huang et al, 2003;Lai and Tarn, 2004), and now CF I m have been shown to interact with the mRNA export receptor NXF1. In addition, shuttling RNA-binding proteins may fulfill different roles in the nucleus and in the cytoplasm.…”
Section: Role Of Rna-binding Shuttling Proteins In Mrna Exportsupporting
confidence: 60%
“…This raises the possibility that multiple and partially redundant adaptor proteins may be responsible for the recruitment of NXF1. Indeed, spliceosomal proteins, including U2AF35 (Zolotukhin et al, 2002) and some members of the SR family of splicing factors, were shown to interact with NXF1 and act as adaptors for NXF1-dependent export of poly(A) mRNAs (Huang and Steitz, 2001;Huang et al, 2003;Lai and Tarn, 2004;Hargous et al, 2006;Tintaru et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been well documented that RNAs that serve as substrates for CTE-mediated export initially interact with the splicing machinery even when they remain completely unspliced (Lu et al 1990;Hammarskjöld 1997). It has also been shown that U2AF65 can stimulate the nuclear export and expression of an unspliced reporter RNA retaining an intron and that exogenously expressed U2AF65 can recruit Tap to mRNP complexes (Zolotukhin et al 2002). These results thus suggest a role for splicing factors in the formation of an export-competent CTE-containing mRNP complex.…”
Section: Discussionmentioning
confidence: 50%